2007
DOI: 10.1248/bpb.30.423
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol [2-Methoxy-4-(2-propenyl)phenol] Prevents 6-Hydroxydopamine-Induced Dopamine Depression and Lipid Peroxidation Inductivity in Mouse Striatum

Abstract: Parkinson disease (PD) is characterized by progressive degeneration of dopaminergic neurons of the nigrostriatal system and dopamine (DA) depletion in the striatum. While the pathogenesis of PD is not clear, damage of dopaminergic neurons by oxygen derived free radicals is considered to be an important contributing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 28 publications
2
60
0
2
Order By: Relevance
“…Eugenol also forms complexes with reduced metals, thus, inhibiting the formation of perferryl ion or iron-oxygen chelate complex as the initiating factor of lipid peroxidation (Ito et al, 2005). Moreover, eugenol acts indirectly by increasing GSH which is an antioxidant itself and plays a pivotal role in reducing lipid peroxides (Kabuto et al, 2007). The present results also revealed that eugenol significantly reduced gastric mucosal NO level, an action that may be involved in its gastroprotective effect.…”
Section: Discussionsupporting
confidence: 61%
“…Eugenol also forms complexes with reduced metals, thus, inhibiting the formation of perferryl ion or iron-oxygen chelate complex as the initiating factor of lipid peroxidation (Ito et al, 2005). Moreover, eugenol acts indirectly by increasing GSH which is an antioxidant itself and plays a pivotal role in reducing lipid peroxides (Kabuto et al, 2007). The present results also revealed that eugenol significantly reduced gastric mucosal NO level, an action that may be involved in its gastroprotective effect.…”
Section: Discussionsupporting
confidence: 61%
“…We also have reported that pre-treatment of eugenol, a naturally occurring phenol extracted from cloves, protects against 6-OHDA-induced depletion of striatal DA by increasing the concentrations of reduced glutathione (GSH) and Asc [8]. Zingerone and eugenol are known to be antioxidants [9][10][11][12] themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, eugenol was previously reported to protect neuronal cells from excitotoxic and oxidative injury in mouse cortical cultures (18). Furthermore, it prevented from 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in mouse striatum (19) and provided a neuroprotective effect against hippocampal CA1 neuronal ischemia-induced injury in gerbils (20). It also proved to protect against acrylamide-induced neuropathy (21) and chlorpyrifos-induced brain toxicity (12) in rats, which may at least in part be attributed to its antioxidative stress activity.…”
mentioning
confidence: 99%